The Confidence Level of Applied Foreign Languages Students In English Public Speaking - Nadira Febiela Rosyadi; Dea Dewanti; Nida Fadhilah; Fitri Alfarisy (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to determine: (1) the confidence level of Diponegoro University Applied Foreign Languages English Students Class of 2019 – 2020 with public speaking in English; (2) the reason for the insecurity of Diponegoro University Applied Foreign Language English Students Class of 2019 – 2020 with public speaking in English; (3) solutions to the lack of confidence for English students of Diponegoro University Applied Foreign Languages Class of 2019 – 2020 with public speaking in English. This research uses a quantitative approach with an exploratory type. Determination of research subjects using simple random sampling techniques. The sample in this study was 54 students of applied foreign language class 2019-2020 specializing in English at Diponegoro University. The instrument used is a questionnaire. The questionnaire used in this study is closed and answered directly by the respondent. The measuring instrument that will be used in this study is to use a modified Likert scale with four alternative answers, namely strongly agree (SS), agree (S), disagree (TS), and strongly disagree (STS). The results showed that the highest number of 54 respondents Students of Applied Foreign Languages at Diponegoro University is Lack of Preparation with average 3.18, while reason chosen with the lowest number of respondents is A Feeling of Incapacity with average 2. The solutions for three highest reasons. There are lack of preparation, the solution is break down the practice into smaller, more doable parts in order to reduce stress and increase performance, the practice should be done in small, manageable pieces. Then stage fright, rather than focusing on the audience, concentrate on the topic. People are more interested in new knowledge than in how it is delivered. They may be unaware of the students' anxiousness. And the last is inferiority or low self-esteem, appreciate what the students achieved. Give pat at the back following the speech or presentation